Validation of Sustainable Development Practices Scale Using the Bayesian Approach to Item Response Theory - Martin Hernani Merino; Enver Gerald Tarazona Vargas; Antonieta Hamann Pastorino; José Afonso Mazzon (Tržište, 2014)
There has been growing recognition of the importance of creating performance measurement tools for the economic, social and environmental management of micro and small enterprise (MSE). In this context, this study aims to validate an instrument to assess perceptions of sustainable development practices by MSEs by means of a Graded Response Model (GRM) with a Bayesian approach to Item Response Theory (IRT). The results based on a sample of 506 university students in Peru, suggest that a valid measurement instrument was achieved. At the end of the paper, methodological and managerial contributions are presented.